Interactive lecture demonstration and inquiry-based instruction in addressing students' misconceptions in electric circuits - CASIMIRO, MARK ANTHONY (Archīum Ateneo, 2017)
The study aimed to compare the effectiveness of two methods- Interactive Lecture Demonstration and Inquiry-Based Instruction in addressing students' misconceptions in electric circuits. This study used the mixed method which involved both quantitative (quasi-experimental) and qualitative (focus group discussion). The main data of this was the pretest and posttest results of the two groups (DIRECT v1.2). The results showed that there was no significant difference in the performance of the students in the posttest. In conclusion, these two methods are effective in addressing misconceptions in electric circuit.